THE ROLE OF SOCIAL FACTORS IN THE ACCEPTANCE OF ARTIFICIAL INTELLIGENCE-BASED SERVICES: THE EXAMPLE OF THE BANKING SECTOR OF BOSNIA AND HERZEGOVINA (The South East European Journal of Economics and Business, 2024)
In times when AI’s development and research is moving at an unprecedented speed, this paper explores its role in retail banking. The results presented are part of a wider research of market readiness and AI acceptance, especially in developing economies. The research was conducted in Bosnia and Herzegovina (B&H). The quantitative portion consisted of a survey completed by 671 respondents. This paper focuses on the influence of social factors (perceived humanness, perceived social interactivity, and perceived social presence) on the attitudes towards – and subsequently acceptance of - AI-based services. Chatbots, specifically ChatGPT-4, were the technology the research focused on. The results indicate that perceived humanness and perceived social interactivity have a positive effect on attitudes – and acceptance – of AI-based services. This research could not prove that there is a positive relationship between social presence and attitudes towards AI-based services. The positive relationship between attitude and acceptance was proven as well.